Implementing injury prevention strategies in community-based youth football: The role of parents, coaches, and organizational leaders - Jillian E. Urban; Kimberly D. Wiseman; Justin B. Moore; Madison E. Marks; Ty D. Holcomb; Braydon B. Lazzara; Christopher M. Miles; Laura A. Flashman; Joel D. Stitzel; Kristie L. Foley (PLoS ONE, 2025)
The objective of the study was to gather perspectives and experiences of parents, coaches, and organizational leaders surrounding safety in youth football as it relates to roles and responsibilities of the coach. Parents (n = 13) and coaches (n = 10) of two youth football teams participated in separate, team-specific monthly focus groups to gather their perspectives and experiences surrounding youth football safety. Six organizational leaders participated in one-on-one interviews. Focus groups were coded in Atlas.ti. Interviews were summarized using methods of rapid analysis. Data from focus groups and interviews were integrated and analyzed for thematic content. Parents, coaches, and organizational leaders regarded the youth football coach’s role as “so much more than football,” often serving as role models, mentors, and father figures to athletes. Parents place trust in their son’s coaches and expect them to have knowledge and skills necessary to coach football and teach proper skills to prevent injuries. Organizational leaders set expectations of coaches but recognized the coaches’ autonomy in determining team activities and responsibility for safety. Coaches who teach techniques that are not aligned with current practices and coaches who prioritize winning over safety were identified as concerns for safety. Results demonstrate the important role coaches play in the personal and technical skill development and safety of youth football players and should be considered in the development and implementation of evidence-based strategies to improve safety in community-based sports.